Travels Through Heterotopia: The Textual Realms of Patrick Modiano's Rue des Boutiques Obscures and Mikhail Kuraev's Kapitan Dikshtein - Vitaly Chernetsky (Studies in 20th & 21st Century Literature, 1998)
Within contemporary prose, one distinct mode or paradigm that can be discerned is constituted by the texts that daringly tackle the dark, suppressed, erased parts of our history and mentality; however, they approach this task not by way of self-righteous denunciatory investigations, but by provocatively problematizing the most established everyday facts, by depriving the reader of the possibility of even conceiving any firm ground of the stable construct of an origin or a self-identification—historically and culturally. Their irreverent and playful deconstruction of the all-pervasive national cultural mythologies has mounted a powerful challenge to ideological constructs big and small. This article considers two representative examples of texts of this kind, which the author proposes to call heterotopic: Patrick Modiano's Rue des Boutiques Obscures and Mikhail Kuraev's Kapitan Dikshtein. It offers an attempt at defining this paradigm through a reading of these two novels, drawing upon Michel Foucault's usage of the term "heterotopia" for the purpose of designating the "other" cultural spaces of our civilization, as well as on Deleuze and Guattari's concept of "minor literature" and the work of several other theorists. The texts of the kind exemplified by these two novels are considered as an instance of successful partaking in the project of cognitive mapping, which has been proposed by Fredric Jameson and others as the positive political edge of postmodern culture.
Keywords: heterotopia; Patrick Modiano; contemporary prose; dark; suppressed; erased; history; mentality; self-righteous; self-identification; national cultural mythologies; ideological constructs; heterotopic; Rue des Boutiques Obscures; Mikhail Kuraev; Kapitan Dikshtein; Michel Foucault; other; cultural spaces; civilization; Deleuze and Guattari; minor literature; Fredric Jameson; cognitive mapping; postmodern culture; political